VEXAS Syndrome: A Comprehensive Review of Clinical Mimickers and Differential Diagnosis at the Rheumatology–Haematology Interface - Aleksandrowicz, Hanna; Kalinowska, Zuzanna; Sokołowska , Julia; Karska, Karolina; Grunwald, Katarzyna; Dawidowicz, Marcel (Journal of Education, Health and Sport, 2026)
VEXAS syndrome is a newly described autoimmune disorder in adults caused by a somatic mutation in the UBA1 gene located on the X chromosome, occurring almost exclusively in older men. The disease combines features of severe chronic inflammation with hematopoietic disorders, resulting in a heterogeneous and multi-organ clinical picture and frequent diagnostic difficulties. The aim of this study is to present the characteristics of VEXAS syndrome and discuss the most important diseases mimicking its course, with particular emphasis on differential diagnosis. The clinical picture of the syndrome includes recurrent fever, neutrophilic skin lesions, chondritis, vasculitis, lung involvement, and an increased tendency to thrombosis. Haematological abnormalities, primarily macrocytic anaemia and thrombocytopenia, often coexisting with myelodysplastic syndromes, are an integral part of the disease. A characteristic, though not pathognomonic, finding is the presence of cytoplasmic vacuoles in myeloid and erythroid precursors in the bone marrow. VEXAS syndrome can mimic many rheumatological, autoinflammatory, and haematological diseases, such as recurrent chondritis, Sweet’s syndrome, or systemic vasculitis, and its course is often characterized by resistance to standard immunosuppressive treatment. Including VEXAS syndrome in the differential diagnosis of older men with unexplained inflammation and macrocytosis is crucial for shortening the time to diagnosis and implementing appropriate treatment.